Carbon Stock in Sediments of Mangrove Ecosystems in Pangkalan Jambi Village, Bengkalis Regency - Furqan, M. Alief; Amin, Bintal; Nursyirwani, Nursyirwani (Jurnal Natur Indonesia, 2025)
The study on carbon reserves in sediment within Pangkalan Jambi Village, Bengkalis Regency's mangrove ecosystem, was conducted from June to 2024. This research aimed to analyze carbon reserves in the sediment of the mangrove ecosystem in Pangkalan Jambi Village, Bengkalis Regency, Riau Province. The study employed field survey methods and laboratory analyses, focusing on three stations with varying mangrove densities. Results revealed nine mangrove species, dominated by Rhizophora mucronata. The average mangrove density was 2,611 individuals/ha, with a carbon reserve of 43.25 tons/ha across all stations. The study found a positive correlation (r = 0.528) between mangrove density and carbon reserves, explaining 27.98% of the total variation. Furthermore, carbon reserves showed no significant differences across sediment depths. These findings emphasize the importance of mangrove conservation for carbon storage, contributing to climate change mitigation. Further biomass and species-specific carbon storage research is recommended to optimize mangrove management strategies.